2019
DOI: 10.1088/1755-1315/287/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of resistant Salmonella spp. isolated from raw meat and liver of cattle in the Wa Municipality of Ghana

Abstract: This study was carried out to determine the prevalence of resistant Salmonella spp. isolated from meat (beef) and liver of cattle in the Wa, Municipality of Ghana. Isolation of Salmonella spp. was done according to the USA-FDA Bacteriological Analytical Manual. Antibiotic susceptibility test was performed using the disc diffusion method and the results interpreted using the CLSI guidelines. Antibiotic residues determination was carried out using Premi®Test Kit. Liver samples 32%(16/50) were more contaminated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
2
6
2
2
Order By: Relevance
“…This variation might be due to the differences in the hygienic and sanitary practices in the butcher shops especially poor hand washing practices. Studies conducted in Malaysia [7], Ghana [33] and Jimma [34] showed the prevalence of salmonella species to be 10%, 30%, and 11.3% respectively which were higher than the current study. This difference might be due to hygiene and sanitation practice, methodology differences in sample collection and processing procedure.…”
Section: Plos Onecontrasting
confidence: 90%
“…This variation might be due to the differences in the hygienic and sanitary practices in the butcher shops especially poor hand washing practices. Studies conducted in Malaysia [7], Ghana [33] and Jimma [34] showed the prevalence of salmonella species to be 10%, 30%, and 11.3% respectively which were higher than the current study. This difference might be due to hygiene and sanitation practice, methodology differences in sample collection and processing procedure.…”
Section: Plos Onecontrasting
confidence: 90%
“…An intermediate resistance of 2(18.2%) was also found for Ampicillin. On the other hand, Interestingly all of the isolates were 100% susceptible to gentamycine,cipro oxacin,tetracycline and ceftraxione.This is in line with the study conducted in Ghana (66).In addition 7(63.6%) and 9(81.8%) exhibited susceptibility to Tetracycline and Trimethoprim-sulfamethoxazole respectively. This result is also in aligning with study done in Gondar, Ethiopia.…”
Section: Resultssupporting
confidence: 90%
“…A study conducted in Mexico, Latin America on the prevalence and antibiotic susceptibility pattern of Salmonella on raw meat showed high levels of resistance to ampicillin (66.7% of isolates), tetracycline (61.3%), and chloramphenicol (64.5%) and low levels of resistance to cefotaxime (0%), gentamicin (3.2%), and kanamycin (4.3%) (26). A study conducted in the Wa Municipality of Ghana on Prevalence of Salmonella species isolated from raw meat and liver of cattle highly resistant to teicoplanin (96.77%) but susceptible to chloramphenicol (100%), cipro oxacin (100%), tetracycline (100%), suphamethoxazole/ trimethoprim (100%), amoxicillin/clavulanic acid (93.55%), ceftriaxone (93.55%) and gentamicin (83.87%) (66).Another study in Addis Ababa, Ethiopia shows about 25% of Salmonella species were found resistant to ampicillin. Besides, 9% of Salmonella species and 2% of E. coli O157:H7 isolates were found to be resistant to ceftriaxone (15).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of Salmonella in beef samples in our research study is higher as compared to previous research studies [33][34][35][36]. However, some research studies have reported more than 60% prevalence in beef samples [37][38][39][40]. The Salmonella prevalence in beef is much lower in developed countries like USA due to strict control measures.…”
Section: Discussioncontrasting
confidence: 71%